Quality cues and agglomeration benefits in the Beijing Hotel industry. - Khoo, Ke Hui. (2008)
The project seeks to give an understanding about how quality cues and agglomeration will affect the quantity demanded of hotel rooms and also the pricing strategies by the hotel management.